2013
DOI: 10.5860/lrts.57n1.118
|View full text |Cite
|
Sign up to set email alerts
|

Technical Services Transparency

Abstract: Technical services departments in academic librariesA cademic libraries now provide patrons with large numbers of electronic resources. As the number of resources grows, so does the potential number of breakdowns in access. This potential for problems means communication is vital between the technical services staff who manage these resources and the public services staff who interact with patrons.The Oxford English Dictionary defined communication as the transmission or exchange of information, knowledge, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The authors identify several benefits that came with the adoption of a centralized system for documenting and sharing procedures: the ready availability of easily shared documentation, the ease of updating wiki pages within the portal, and the institution of a habit of creating documentation (Diffin, Coogan, & Fu, 2013). In the same year, Bazeley and Yoose (2013) reported on using LibGuides software to develop an online home for technical services documentation at Miami University Libraries, highlighting the site as a valuable communication mechanism not only within technical services but between technical services and public services. Efforts to consider this site for inclusion on the following list were unsuccessful, as it does not appear to be available to the public at the time of this writing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors identify several benefits that came with the adoption of a centralized system for documenting and sharing procedures: the ready availability of easily shared documentation, the ease of updating wiki pages within the portal, and the institution of a habit of creating documentation (Diffin, Coogan, & Fu, 2013). In the same year, Bazeley and Yoose (2013) reported on using LibGuides software to develop an online home for technical services documentation at Miami University Libraries, highlighting the site as a valuable communication mechanism not only within technical services but between technical services and public services. Efforts to consider this site for inclusion on the following list were unsuccessful, as it does not appear to be available to the public at the time of this writing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An examination of a handful of currently available technical services portals revealed that Confluence is another widely used system. The literature also indicates the use of LibGuides for this purpose; an informal survey of available portals shows limited adoption of this system in practice (Bazeley & Yoose, 2013).…”
Section: Library-based Local Documentation Portalsmentioning
confidence: 99%